Neottia milinensis (Orchidaceae: Neottieae), a new species from Xizang, China - Lei, Jia-Jun; Zhang, Xin; Jin, Xiao-Hua (Phytotaxa, 2023)
Neottia milinensis (Orchidaceae), a new species from Milin, Xizang, China, is described and illustrated based on morphological characters and molecular data. The new species is similar to N. camtschatea and N. tenii, but differs from them by having pubescent stem, slender pedicel, lip 8 mm long without a pair of auricles at base, lobelets triangular and less than 1/3 of lip. Molecular phylogenetics indicated that N. milinensis is close to N. camtschatea.